Hepcidin as a possible marker in determination of malignancy degree and sensitivity of breast cancer cells to cytostatic drugs - Yalovenko, T.M.; Todor, I.M.; Lukianova, N.Y.; Chekhun, V.F. (Experimental Oncology, 2016)
Aim: To investigate the role of hepcidin (Hepc) in the formation of cells malignant phenotype in vitro and its expression in the dyna mics of growth of Walker-256 carcinosarcoma with different sensitivity to doxorubicin (Dox). Materials and Methods: The cell lines used in the analysis included T47D, MCF-7, MDA-MB-231, MDA-MB-468, MCF/CP, and MCF/Dox. Hepc expression was studied by immunocytochemical method. “Free” iron content was determined by EPR spectroscopy. Determination of Hepc expression in homogenates of tumor tissue and in blood serum of rats with Dox-sensitive and -resistant Walker-256 carcinosarcoma was performed. Results: It was found that Hepc levels in breast cancer (BC) cells with high degree of malignancy (MDA-MB-231, MDAMB-468) and drug-resistant phenotype (MCF/CP, MCF/Dox) were by 1.5–2 times higher (p < 0.05) in comparison with sensitive and less malignant BC cells. The development of drug-resistant phenotype in Walker-256 carcinosarcoma cells was accompanied by increasing of Hepc and “free” iron content (by 2.4 and 1.2 times, respectively). Conclusion: The data of in vitro and in vivo research evidenced on involvement of Hepc in formation of BC cells malignant phenotype and their resistance to Dox.